(untitled) (Studia Prawnicze / The Legal Studies, 2013)
Pozaustawowe kontratypy są konstrukcją teoretyczną (koncepcją) funk-cjonującą w polskim prawie karnym praktycznie od początku funkcjonowania samych kontratypów. Pomimo tego, że te ostatnie doczekały się licznych monografi i, artykułów i innych opracowań naukowych, to tego samego nie można powiedzieć o samych pozaustawowych kontratypach. Wielu autorów poprzestaje na wygodnym dogmacie o dopuszczalności „instytucji” pozaustawowych kontratypów, a następnie przystępuje do wymienienia tych okoliczności wraz ze wskazaniem ich „znamion”. Tylko nieliczni poddają pod wątpliwość zasadność tej konstrukcji, jednak i ci nie podejmują się kompleksowej analizy tego problemu. W związku z tym postanowiłem dokonać syntezy dość mocno rozczłonkowanych poglądów na temat pozaustawowych kontratypów, tak aby wskazać na główne mankamenty tej koncepcji. Liczę, że dzięki temu dyskusja w tym zakresie dopiero się rozpocznie, co pozwoli lepiej zrozumieć tę „instytucję” i usunąć jej problemy. This article is devoted to analyse outside statutory of factors excluding criminal responsibility conception. Nowadays Polish jurisprudence quite widely accepts this one, not based on act conception. Only a few notice the shortcomings of outside of statutory factors excluding criminal responsibility. Nevertheless, not many make this topic on a deeper reflection. The article attempts to collect the views on this subject in existing polish jurisprudence. It should be noted, that this views are fragmented in numerous articles, books and commentaries. Therefore, an assessment of the concept of outside statutory of factors excluding criminal responsibility which releate to: the function of criminal law, nullum crimen sine lege rule, the separation of powers rule, protection the victim rights and the contents of art. 17 k.p.k. Furthermore, the problem of definiteness constituent elements of outside statutory of the factors excluding criminal responsibility was outlined. It was also presented what behaviors qualify as outside statutory of the factors excluding criminal responsibility by individual representatives of jurisprudence. As a result, the validity of conception of outside statutory of the factors excluding criminal responsibility seems to be fairly questionable.